Indonesian Rheumatology Association (IRA) Recommendations for Diagnosis and Management of Glucocorticoid-induced Osteoporosis - Bagus Putu Putra Suryana; Rudy Hidayat; Laniyati Hamijoyo; Radiyati Umi Partan; Yulyani Werdiningsih; Surya Darma; RM Suryo Anggoro; Anna Ariane; Faisal Parlindungan; Mirza Zaka Pratama; Harry Isbagio; Handono Halim; Cesarius Singgih Wahono; Sumariyono (Indonesian Journal of Rheumatology, 2022)
Background: Patients receiving long-term glucocorticoid therapy are at risk of developing GIOP. However, until today, there is still no guideline that specifically explains how to diagnose and manage GIOP patients in Indonesia. Methods: 10 selected rheumatologists from the Indonesian Rheumatologist Association (IRA) made recommendations based on key questions formed by a steering committee from IRA. These recommendation materials were taken from several online databases such as Pubmed, Science Direct, and Cochrane. Level of evidence and grades of recommendation were then assigned, and every member of the panelist team will assign a score for the level of agreement. Results: A total of 17 recommendations regarding screening, prevention, diagnosis, therapy, and monitoring for GIOP were made. Conclusion: These recommendations can be used for adult patients receiving long-term glucocorticoids with or at risk of developing GIOP. The prevention measure, diagnostic, therapy, and monitoring algorithm in this recommendation are all created with the consideration of Indonesia’s clinical setting, facility, and drug availability.